A Novel approach for Agrobacterium-mediated germ line transformation of Indian Bread wheat (Triticum aestivum) and Pasta wheat (Triticum durum) - Chugh, Archana; Vikrant, S; Mahalakshmi, Akella; Khurana, Paramjit (Journal of Phytology, 2012)
Recalcitrance of wheat towards tissue culture procedures has hampered the wide use of conventional transformation techniques for its improvement. In the present study, a novel, non-tissue culture, cost effective approach has been established for the introduction of transgenes in wheat. Dry, mature seeds of two Indian varieties of wheat, Triticum aestivum cv. HD2329 (bread wheat), and Triticum durum cv. PDW215 (pasta wheat), were co-cultivated with Agrobacterium strain GV2260 (p35SGUSINT) and LBA4404 (pCAMBIA 3301), respectively, in the presence of 200 Î¼M acetosyringone. The plantlets testing gus positive were raised till maturity in garden pots. T0 lines were screened by PCR for presence of selectable markers in the transformed plants followed by confirmation with Southern hybridization. In bread wheat, nptII was detected in five primary transformed lines (T0) (ws1, ws2, ws3, ws4, ws5) and the bar gene in three putatively transformed durum wheat lines (wsb1, wsb2, wsb3). The transformation efficiency was calculated as 1.16%, and 0.84% for T. aestivum and T. durum, respectively.Â 